2007
DOI: 10.1186/1471-2474-8-1
|View full text |Cite
|
Sign up to set email alerts
|

VEGF, FGF1, FGF2 and EGF gene polymorphisms and psoriatic arthritis

Abstract: BackgroundAngiogenesis appears to be a first-order event in psoriatic arthritis (PsA). Among angiogenic factors, the cytokines vascular endothelial growth factor (VEGF), epidermal growth factor (EGF), and fibroblast growth factors 1 and 2 (FGF1 and FGF2) play a central role in the initiation of angiogenesis. Most of these cytokines have been shown to be upregulated in or associated with psoriasis, rheumatoid arthritis (RA) or ankylosing spondylitis (AS). As these diseases share common susceptibility associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
100
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(108 citation statements)
references
References 34 publications
6
100
0
2
Order By: Relevance
“…The gene is highly polymorphic, and several single nucleotide polymorphisms (SNPs) have been associated with altered gene expression and higher VEGF plasma levels (3-7). In addition, previous studies have revealed a correlation with cancer development and progression (8)(9)(10)(11), as well as with Behcet's disease, adult respiratory distress syndrome, rheumatoid arthritis and psoriatic arthritis (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…The gene is highly polymorphic, and several single nucleotide polymorphisms (SNPs) have been associated with altered gene expression and higher VEGF plasma levels (3-7). In addition, previous studies have revealed a correlation with cancer development and progression (8)(9)(10)(11), as well as with Behcet's disease, adult respiratory distress syndrome, rheumatoid arthritis and psoriatic arthritis (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Ten studies were identified by electronic and manual searching and all 10 were selected for full-text review based on title and abstract details (Young et al, 2004(Young et al, , 2006Barile et al, 2006;Butt et al, 2007;Lee et al, 2008;Stefanaki et al, 2008;Wang et al, 2008;Wongpiyabovorn et al, 2008;Wu et al, 2010;Zablotna et al, 2013). However, 3 of the 10 were excluded because they had no control group or did not contain genotype data (Young et al, 2006;Lee et al, 2008;Stefanaki et al, 2008).…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
“…However, 3 of the 10 were excluded because they had no control group or did not contain genotype data (Young et al, 2006;Lee et al, 2008;Stefanaki et al, 2008). Thus, 7 studies met the study inclusion criteria, and these studies included a total 1956 subjects (psoriasis 665, controls 1291) and consisted of European and Asian populations (Young et al, 2004;Barile et al, 2006;Butt et al, 2007;Wang et al, 2008;Wongpiyabovorn et al, 2008;Wu et al, 2010;Zablotna et al, 2013) (Table 1).…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Níveis aumentados, tanto no soro quanto na sinóvia, já foram relatados em pacientes com artrite reumatoide, relacionando o aumento com a doença inicial e maior destruição sinovial (Ishikawa et al, 2011 (Butt et al, 2006;Thomas et al, 2000) e no sangue de pacientes com esclerose sistêmica e DM (Kadono et al, 1996).…”
Section: Lista De Figurasunclassified